(untitled) (Development Service Industry Management, 2025)
In the context of the latest challenges, including the intensification of the pace of life, global shocks caused by the pandemic and war, the psychological state of modern man is undergoing significant negative influences, which significantly actualizes the search for effective methods of its harmonization. Especially effective in terms of preserving and improving mental health is the use of tourism tools in combination with the methods of practical psychology. This study is devoted to the systematization of the characteristic features of travel therapy, psychological tourism, transformational and existential travels aimed at preserving human mental health according to the following parameters: focus, methodology, professional support, duration and intensity, target audience, and substantiation of the role of travel therapy in improving the psychological well-being of people in difficult life situations. At present, this is of particular importance for Ukraine, given the growing relevance of the problem of preserving the nation’s mental health in wartime and post-war. The paper provides a detailed analysis of foreign and domestic publications on the impact of tourist travel on mental health and happiness. Particular attention is paid to the analysis of psychological mechanisms that contribute to the transformation of the individual during travel and the impact of the synergy between the restorative properties of travel and psychotherapeutic methods on cognitive and emotional processes. The study opens up prospects for the development of travel therapy programs, taking into account the cultural, economic, social and environmental factors relevant to each period of time, which will affect the effectiveness of this approach in restoring and improving the psychological well-being of the population, and also outlines promising areas for the development of the tourism business, for which an innovative format has been identified, which will allow the development of new business models, social strategies and thereby increase the profitability of its activities.